FinTech solutions for sustainable agricultural value chains: A perspective from smallholder farmers - Rayhan, Md. Johir; Rahman, S. M. Masudur; Mamun, Abdullah Al; Mohammad Saif, Abu Naser; Islam, K. M. Anwarul; Alom, Md. Mahabub; Hafiz, Nusrat (John Wiley and Sons, 2024)
Smallholder farmers in developing nations face multifaceted challenges as they strive to secure fair prices for their agricultural products. With a primary focus on bolstering sustainable agricultural value chains (SAVC), this conceptual paper investigates the transformative potential of Financial Technology (FinTech) solutions. The study synthesizes insights from prior research on SAVC, hurdles faced by smallholder farmers, conventional strategies, and the untapped prospects offered by FinTech solutions in the agricultural sector. Utilizing the PRISMA strategy for comprehensive documentation retrieval, the study underscores the significance of creating a robust SAVC to empower smallholder farmers within the broader value chain landscape. It is found that Agri-FinTech solutions represent a pivotal avenue for advancing living standards and cultivating agricultural sustainability in developing nations. The integration of FinTech solutions for agri-credit mechanisms and product market facilitation catalyzes enabling pre-production financing and ensures fair prices for smallholder farmers in the post-production phase while neutralizing the value chain's exploitation potential. The study advocates for the expeditious adoption of information technology in developing countries, spotlighting the transformative role of Mobile Financial Services (MFS), which fortifies the agriculture sector, ensuring its resilience and responsiveness to the evolving demands of a globalized market. Drawing upon an evaluation of existing literature on FinTech-enhanced agricultural initiatives in developing nations, the study outlines directions for future research and creates a path for a more nuanced understanding of the strategic enhancements necessary to fortify the SAVC, fostering a sustainable and equitable ecosystem for smallholder farmers. © 2024 ERP Environment and John Wiley & Sons Ltd.